2011
DOI: 10.1590/s1678-77572011000600023
|View full text |Cite
|
Sign up to set email alerts
|

Speech therapy for compensatory articulations and velopharyngeal function: a case report

Abstract: 5HFHLYHG -XO\ $FFHSWHG $XJXVW T KH REMHFWLYH RI WKLV VWXG\ ZDV WR GHVFULEH WKH SURFHVV RI LQWHQVLYH VSHHFK WKHUDS\ IRU D \HDUROG FKLOG XVLQJ FRPSHQVDWRU\ DUWLFXODWLRQV ZKLOH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0
41

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(72 citation statements)
references
References 10 publications
2
29
0
41
Order By: Relevance
“…The literature states that the use of mirrors increases the activation of the primary and superior visual areas, contralateral to the limb observed; it is concluded that the activation of brain lateralization is elicited by inverting the visual feedback (mirror) (3) . Tactile strategies are also described, especially in the training of speech, with blowing strategies on the back of the hands to work the direction of airflow in the fricative and affricate phonemes (4) , as well as the use of proprioceptive tools to regulate the positioning of the tongue in some liquid phonemes. Still regarding the training of speech and vocal production, hearing and visual feedback is referred to as facilitators, with recording strategies to further analyze patients (5) and delayed feedback for the speech training of patients with dysfluency (6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature states that the use of mirrors increases the activation of the primary and superior visual areas, contralateral to the limb observed; it is concluded that the activation of brain lateralization is elicited by inverting the visual feedback (mirror) (3) . Tactile strategies are also described, especially in the training of speech, with blowing strategies on the back of the hands to work the direction of airflow in the fricative and affricate phonemes (4) , as well as the use of proprioceptive tools to regulate the positioning of the tongue in some liquid phonemes. Still regarding the training of speech and vocal production, hearing and visual feedback is referred to as facilitators, with recording strategies to further analyze patients (5) and delayed feedback for the speech training of patients with dysfluency (6) .…”
Section: Introductionmentioning
confidence: 99%
“…A nasometer is used to increase visual perception of nasal and oral air flow in the practice of velopharyngeal functioning during speech production. Therapists make speech tasks more difficult, as patients improve their perception of the direction of the oral and nasal air flow (4) . Another technique used as therapeutic methodology, yet rarely described in the field of speech therapy, is the use of electromyographic biofeedback.…”
Section: Introductionmentioning
confidence: 99%
“…A DVF é o termo mais genericamente usado para caracterizar alterações no funcionamento do MVF (KUMMER, 2001;DWORKIN;MARUNICK;KROUSE, 2004;TRINDADE et al, 2005;KUEHN, 2007). A DVF pós-palatoplastia primária geralmente pode ocorrer ou por falta de tecido no palato (insuficiência velofaríngea), ou por erros de aprendizagem no uso do MVF para a fala (PEGORARO-KROOK; AFERRI; UEMEOKA, 2009;BISPO et al, 2011;KUMMER et al, 2012;KUMMER, 2014).…”
Section: Velofaríngeounclassified
“…Contudo, é comum que indivíduos que permaneceram com DVF após a palatoplastia primária possam apresentar ambos os tipos de DVF e nestes casos, é imprescindível que o tratamento utilize um procedimento físico associado à fonoterapia (PEGORARO-KROOK et al, 2010;AFERRI, 2011;BISPO et al, 2011;PEGORARO-KROOK, 2014;KUMMER, 2014 KARNELL, 2001a;PETERSON-FALZONE et al, 2006;KUMMER, 2008;KUMMER, 2014). As articulações compensatórias são desenvolvidas pelo indivíduo em resposta à dificuldade de impor pressão aérea intraoral na cavidade oral fazendo com que este busque outros pontos no trato vocal (geralmente laringe e faringe) onde consiga gerar pressão, necessitando de fonoterapia, de preferência, após a correção estrutural (KUMMER, 2001;PETERSON-FALZONE et al, 2006;KUMMER, 2008;KUMMER, 2014).…”
Section: Velofaríngeounclassified
“…Por outro lado, postergá-lo pode afetar diretamente o desenvolvimento da fala (HENNINGSSON et al, 2008;AGRAWAL, 2009;MITUUTI et al, 2010;BISPO et al, 2011;WILLIAMS et al, 2011;HORTIS-DZIERZBICKA;RADKOWSKA;FUDALEJ, 2012;ABDEL-AZIZ, 2013;CHEN et al, 2013;GUNDLACH et al, 2013;HOPPER et al, 2014;RANDAG;DREISE;RUETTERMANN, 2014). A maioria dos centros mundialmente realiza a palatoplastia entre 6 e 12 meses de idade, pois nesta faixa etária a criança encontrase no início da aquisição de linguagem (ANDRADES et al, 2008;AGRAWAL, 2009;KATZEL et al, 2009;GONGORJAV et al, 2012;ABDEL-AZIZ, 2013;CHEN et al, 2013;HOPPER et al, 2014).…”
unclassified